Biomimetic Methacrylated Gelatin Hydrogel Loaded With Bone Marrow Mesenchymal Stem Cells for Bone Tissue Regeneration - Li, Jun; Wang, Wenzhao; Li, Mingxin; Song, Ping; Lei, Haoyuan; Gui, Xingyu; Zhou, Changchun; Liu, Lei (Frontiers in Bioengineering and Biotechnology, 2021)
Large segment bone defect caused by trauma or tumor is one of the most challenging problems in the orthopedic clinics. Biomimetic materials for bone tissue engineering have developed dramatically in the past few decades. The organic combination of biomimetic materials and stem cells offers new strategies for tissue repair, and the fate of stem cells is closely related to their extracellular matrix (ECM) properties. In this study, a photocrosslinked biomimetic methacrylated gelatin (Bio-GelMA) hydrogel scaffold was prepared to simulate the natural bone extracellular matrix's physical structure and chemical composition, providing a three dimensional (3D) template and extracellular matrix microenvironment. Bone marrow mesenchymal stem cells (BMSCS) were encapsulated in Bio-GelMA scaffolds to examine the therapeutic effects of ECM-loaded cells in a 3D environment simulated for segmental bone defects. In vitro results showed that bio-GelMA had good biocompatibility, sufficient mechanical properties (14.22kPa). Rat segmental bone defect model was constructed in vivo. GelMA-BMSCs suspension was added into PDMS mold with the size of bone defect and photocured as scaffold. BMSC-loaded Bio-GelMA resulted in maximum and robust new bone formation compared to hydrogels alone and stem cell group. In conclusion, the bio-GelMA scaffold can be used as a cell carrier of BMSC to promote the repair of segmental bone defects and has great potential in future clinical applications.